Assessing the Maturity of the “Family Centered Care” Concept: A Review of Concept Analyses Studies - Al-Motlaq, Mohammad; Foster, Mandie; Zgambo, Maggie; Neill, Sarah (Elsevier, 2024)
Background Concept analysis studies play major role in clarifying and operationalizing concepts. This approach has been used to clarify and advance knowledge about the concept of Family Centred Care (FCC). The concept of FCC has been studied by many nursing scholars using different methods. Aim This review aimed to combine outcomes of concept analysis studies to assess the level of maturity of the concept of Family Centred Care. Methods Formal electronic databases (MEDLINE and CINAHL) and informal (Google Scholar) were searched using the terms “Family Centred Care” and “concept analysis”. The Morse concept maturity evaluation approach was used to appraise the retrieved studies. Results 35 studies were identified of which 12 met the inclusion criteria and were included in the analysis. Three studies used Walker and Avant concept analysis methodology, three applied the Rodgers evolutionary model while six applied modified mixed/hybrid approaches. While a few provided a definition of FCC, none have been able to confirm the maturity of the concept. This review summarized the different trials to analyze the concept of FCC supporting the rethinking of the model and emergence of new models such as Child and Family Centred Care (CFCC). Implications Concept analyses should be done periodically to assess the maturity of emerging concepts. Previously published FCC concept analyses manuscripts show the concept has evolved and gained significant recognition and acceptance over time. A clearer definition of FCC supports its positive impact on patient outcomes. A comprehensive FCC tool that can evaluate the effective delivery of FCC is needed.
Keywords: 1110 Nursing; 1114 Paediatrics and Reproductive Medicine; Nursing; 3213 Paediatrics; 4205 Nursing; Concept analysis; Family Centred Care; Children; Family